2017
DOI: 10.1111/bjd.15165
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of wet wrap therapy for patients with atopic dermatitis: a systematic review and meta‐analysis

Abstract: Wet wrap therapy (WWT) consists of topical steroids administered under a layer of wet cotton bandages or garments. Several trials with WWT have reported promising results in atopic dermatitis (AD). However, no systematic review and meta-analysis on its efficacy and safety has been published. Our objective was to conduct a systematic review of the literature on WWT in AD to assess its efficacy and safety. We included randomized controlled trials among patients of all ages with a diagnosis of AD based on predefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 25 publications
0
27
0
4
Order By: Relevance
“…Wet‐wrap medications are highly effective in acute AE and improve tolerance. The use of wet‐wrap dressings with diluted corticosteroids for up to 14 days (usual is rather up to 3 days) may be a safe crisis intervention treatment of severe and/or refractory AE with temporary systemic bioactivity of the corticosteroids as the only reported serious side‐effects . However, this treatment approach is not standardized yet, and the evidence that it is more effective than conventional treatment with topical steroids in AE is not of high quality.…”
Section: Topical Anti‐inflammatory Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Wet‐wrap medications are highly effective in acute AE and improve tolerance. The use of wet‐wrap dressings with diluted corticosteroids for up to 14 days (usual is rather up to 3 days) may be a safe crisis intervention treatment of severe and/or refractory AE with temporary systemic bioactivity of the corticosteroids as the only reported serious side‐effects . However, this treatment approach is not standardized yet, and the evidence that it is more effective than conventional treatment with topical steroids in AE is not of high quality.…”
Section: Topical Anti‐inflammatory Therapymentioning
confidence: 99%
“…The use of wet-wrap dressings with diluted corticosteroids for up to 14 days (usual is rather up to 3 days) may be a safe crisis intervention treatment of severe and/or refractory AE with temporary systemic bioactivity of the corticosteroids as the only reported serious side-effects. [102][103][104][105] However, this treatment approach is not standardized yet, and the evidence that it is more effective than conventional treatment with topical steroids in AE is not of high quality. Simple or occlusive medications in less sensitive skin areas and for brief time periods may also increase efficacy and speed up lesion resolution.…”
Section: Topical Anti-inflammatory Therapymentioning
confidence: 99%
“…One meta‐analysis evaluated wet‐wrap therapy for AE, consisting of topical steroid application under a layer of wet cotton bandages or garments (6 RCTs, 208 participants). A pooled estimate of the efficacy of wet‐wrap therapy could not be calculated due to the high trial heterogeneity.…”
Section: Complementary and Alternative Treatmentsmentioning
confidence: 99%
“…As inflammation dermatoses improve, pruritus tends to decrease . WWT has the added benefit of providing a physical barrier to prevent the child from scratching, although a meta‐analysis of six randomized controlled trials (RCTs) from 2016 demonstrated that the grade of evidence for WWT relieving pruritic symptoms in children with AD is low, suggesting that further studies are needed to establish its efficacy in reducing nocturnal itching . Wet wrap therapy should be limited to less than 1 week at a time because of the risk of mild skin infections such as folliculitus …”
Section: Nonpharmacologic Approachesmentioning
confidence: 99%